Building 'Critical Performativity Engines' for deprived communities: The construction of popular cooperative incubators in Brazil. (September 2014) - Leca, Bernard; Gond, Jean-Pascal; Barin Cruz, Luciano
Although worker cooperatives offer an organizational model that critical management scholars could adopt to demonstrate the utility of their normative ideals, little is known about how academia can contribute to the creation of worker cooperatives. Building on the concept of performativity and the case of the Technological Incubators for Popular Cooperatives in Brazil, we provide an account of constructing incubators for worker cooperatives across multiple universities. Our study uncovers the challenges that scholars face in performing the model of worker cooperatives by cognitively embedding actors within both economic and cooperative principles through teaching. Our results clarify the role of feedback loops, knowledge circulation, and the building of 'chains of translation' in the concrete manufacturing of worker cooperatives, and we show how universities can help develop a multilevel, flexible, and complex support network that enhances the performativity of the worker cooperative model. We advance the concept of a 'critical performativity engine' to describe the process whereby the first method for incubating cooperatives was developed and then translated across settings.